PENGARUH NILAI PRODUK DAN PERSEPSI HARGA TERHADAP KEPUASAN KONSUMEN DAN DAMPAKNYA TERHADAP KESETIAAN PENGGUNA MEREK OLI TOP ONE - M. Fatchurrizal, 12.05.51.0181; Santosa, Eric (Students' Journal of Economic and Management, 2018)
The aim of this study was to analyze the influence of the value of the product and the perception of price on consumer satisfaction and its impact on the brand loyalty Oli Top One. The population of this study is consumers who buy Oli Top One in the city of Semarang. The sample in this study as many as 100 people. The sampling technique used purposive sampling. The criteria for the samples in this study are customers who buy and use lubricating oil products Top One of at least twice already. The analysis tool used is the test of validity, reliability and multiple linear regression. The results of the analysis can be concluded that: The value of the product positively affects customer satisfaction. Perception prices positively affects customer satisfaction. Value product positively affects brand loyalty. Perception positive effect on the price of brand loyalty. Consumer satisfaction has positive influence on brand loyalty. Consumer satisfaction is not as mediating variables influence the value of the product to the brand loyalty. Consumer satisfaction is not as mediating variables influence price perception towards brand loyalty.Keywords: the value of the product, the perception of price, consumer satisfaction and brand loyalty.